Instituting Public Health Laboratory Surveillance for Methicillin-resistant Staphylococcus aureus (MRSA), Extended-Spectrum Β Lactamase producing Enterobacteriaceae (ESBL), and Carbapenem-resistant Enterobacteriaceae (CRE) in a Large Metropolitan County. (4th October 2017) - O'Donnell, Kathleen; Handler, Eric; Zahn, Matthew
Abstract: Background: The community spread of multi drug-resistant organisms (MDROs) presents a significant local public health threat. The Orange County Health Care Agency (OCHCA) is collaborating with the Centers for Disease Control and Prevention (CDC) on a countywide decolonization collaborative involving 38 healthcare facilities. To characterize our county's MDRO epidemiology and assess the effectiveness of these efforts, the OCHCA instituted local mandatory reporting for Methicillin-resistant Staphylococcus aureus (MRSA), extended-spectrum β lactamase producing Enterobacteriaceae (ESBL), and carbapenem-resistant Enterobacteriaceae (CRE). Methods: In July 2016 a health officer order was signed requiring all laboratories serving any county hospital, long-term acute care hospital (LTAC), or skilled nursing facility (SNF), to report all ESBL- and CRE-positive laboratory results, and all inpatient MRSA-positive reports to OCHCA. For this analysis, we reviewed reports received from July 2016 to March 2017. Results: 12 laboratories serving 24 of 32 hospitals, all 3 LTACs, and 65 of 72 SNFs have been routinely reporting electronically. To date, we validated MDRO data from 13 hospitals, all LTACs, and all SNFs by comparing with parallel reporting systems. Validated hospitals reported 98 MRSA- and 115 ESBL-positive blood culture events. SNFs reported 754 ESBL-culture positive events from all culture types. Conclusion: MDROs are significant causes of invasive disease in Orange County. ESBL colonization or infection was commonly identified in SNF residents, highlighting the need for improved infection control and antibiotic use in these settings. Community-wide surveillance provided objective data to assess the magnitude of MDROs. Local public health surveillance for CRE, ESBL, and MRSA can be effectively instituted in a large community, but is resource-intensive and requires extensive facility outreach. Disclosures: All authors: No reported disclosures.